Patterns of Eating Associated with Sleep Characteristics: A Pilot Study among Individuals of Mexican Descent at the US-Mexico Border. Issue 2 (4th March 2022) - Ghani, Sadia B.; Delgadillo, Marcos E.; Granados, Karla; Okuagu, Ashley C.; Wills, Chloe C. A.; Alfonso-Miller, Pamela; Buxton, Orfeu M.; Patel, Sanjay R.; Ruiz, John; Parthasarathy, Sairam; Haynes, Patricia L.; Molina, Patricia; et al.
ABSTRACT: Introduction : Previous studies have linked sleep to risk of diabetes and obesity, at least partially via alterations in food intake. Diabetes and obesity are common among Hispanics/Latinos, and studies are needed to better clarify the role of sleep in health among this group. Utilizing the revised TFEQ-R-18, this study will examine whether eating behaviors such as cognitive restraint, emotional eating and uncontrolled eating are related to self-reported sleep experiences. Specifically, we hypothesized that poor eating habits would be associated with (1) more insomnia symptoms, (2) overall worse sleep quality, (3) increased daytime sleepiness, and (4) shorter sleep duration. Methods: Data were collected from N = 100 adults (age 18–60, 47% female) of Mexican descent in the city of Nogales, AZ (34% not born in the US). Surveys were presented in English or Spanish. Eating Patterns were assessed with the Three-Factor Eating Questionnaire (TFEQ), which resulted in a total score and subscales for "cognitive restraint, " "uncontrolled eating, " and "emotional eating." Insomnia was assessed with the use of the Insomnia Severity Index (ISI), Sleepiness with the use of the Epworth Sleepiness Scale (ESS), Sleep quality with the use of the Pittsburgh Sleep Quality Index (PSQI), and weekday and weekend sleep duration with the use of the Sleep Timing Questionnaire (STQ). Covariates included age, sex, Body Mass Index (BMI), education and immigrant status. Results: Overall TFEQ score (problematic eating) was positively associated with greater insomnia, poorer sleep quality, more sleepiness, and less weekend (but not weekday) sleep. Mean TFEQ score in the sample was 18.7 (range 0–51). In adjusted analyses, every point on the TFEQ was associated with 0.6 ISI points, 0.8 PSQI points, 0.5 ESS points, and 1.1 minutes of less weekend sleep duration. Regarding subscale scores, relationships were generally seenbetween sleep and emotional eating and unrestricted eating, and not cognitive restraint. Conclusions: Greater insomnia, poorer sleep quality, increased daytime sleepiness and decreased weekend sleep duration were associated with eating patterns at the US-Mexico border, particularly in the area of unrestricted eating and emotional eating. This suggests possible mechanisms linking sleep and obesity in Hispanic/Latinos.